NILAI KERUKUNAN PADA CERITA RAKYAT DAYUHAN-INTINGAN DI KABUPATEN TAPIN KALIMANTAN SELATAN - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Communities often have traditions that are the source of values and norms of reference for the lives of their citizens. Among the traditions that hold the values of social life are oral traditions of folklore. This research aims to reveal content content and values of harmony in Dayuhan and Intingan story that developed in Banua Halat Village, Tapin, South Kalimantan. This study uses hermeneutic and ethnographic methods. The findings indicate that Dayuhan and Intingan folklore is the source of norm for the harmony between Banjar Tribe and Meratus Dayak Tribe. Dayuhan and Intingan are two brothers, siblings who, despite their different beliefs, keep the brotherhood among them. The values of harmony in the Dayuhan and Intingan story are among others: unity of humanity, mutual trust, fulfillment, tolerance, cooperation, mutual respect, and conflict resolution. This story inspires Banjar and Dayak people that they are brothers, therefore must maintain harmony between them. The government, especially the Ministry of Religious Affairs, can use this folklore as a material for fostering religious harmony in the community.